Hubungan Antara Komunikasi Antarpersonal Dengan Kepuasan Kerja Pada Karyawan Di Perusahaan Daerah Air Minum (PDAM) Surakarta - Yanuarika, Aristri, Drs. Mohammad Amir, M.Si (2016)
Basically the job satisfaction is an important issue for the company. Job satisfaction is also expected by the Regional Water Company (PDAM). One of the factors that affect job satisfaction is interpersonal communication. The purpose of this research is to determine the relationship between interpersonal communication with employee job satisfaction of PDAM Surakarta, level of interpersonal communication, job satisfaction, and interpersonal communication major contribution to job satisfaction. The population in this study were all employees of PDAM Surakarta amounted to 365 people, with a sample of 75 people. Sampling using random cluster sampling. Measuring instrument using a scale of interpersonal communication and job satisfaction. The technique used in this study is the product moment correlation using SPSS for Windows. The research showed a correlation coefficient of 0.451 with p = 0.000 (p ≤ 0.01). This means that there is a significant positive relationship between interpersonal communication with employee job satisfaction of PDAM Surakarta. Interpersonal communication is high. The result of the category of job satisfaction is high. Interpersonal communication contributes to job satisfaction in employees PDAM Surakarta at 20.3%, the remaining 79.7% is influenced by other variables.